Proteomic Analysis of Auricularia auricula-judae Under Freezing Treatment Revealed Proteins and Pathways Associated With Melanin Reduction - Li, Jiawen; Li, Ziwei; Zhao, Tong; Yan, Xiufeng; Pang, Qiuying (Frontiers in Microbiology, 2021)
Auricularia auricula-judae is an edible nutrient-rich mushroom, which is a traditional medicinal resource in China. It is known that the environment stimuli will affect the production of A. auricula-judae melanin, but the mechanism on the effects of freezing treatment in melanin accumulation remains unknow. In present study, the synthesis of melanin in A. auricula-judae were analyzed by physiological assays and proteomic approach. Our finding showed that the longer freezing treatment cause the lighter color of A. auricula-judae fruiting bodies. The proteomic analysis showed proteins involved in glycolysis/gluconeogenesis, tyrosine metabolism, ribosome and arginine biosynthesis might contribute to the color differences in the A. auricula-judae after freezing treatment. This work will be expected to provide a valuable information of the physiological and molecular mechanisms of freezing treatment on the color quality of A. auricula-judae.